ANALISIS POTENSI DAN STRATEGI PENGEMBANGAN JAMU INSTAN DI KABUPATEN KARANGANYAR - Nuning Setyowati; Rhina Uchyani Fajarningsih; Raden Kunto Adi (Caraka Tani: Journal of Sustainable Agriculture, 2012)
This study aims to map the agro-rural instant herbal medicine in Karanganyar District, identifying rank (potential) of rural agro instant herbal medicine in the District of Karanganyar, formulating development strategies agroindusti rural development strategy and identify herbal instant maps of rural agro-industry business chain instant herbal medicine in the District of Karanganyar. The research method using descriptive analytical method, the technique of collecting data using surveys and focus group techniques. Analysis tools used include: Comparative Exponential Method, Borda method, SWOT and Value Chain. The results showed that the agro-instant herbal medicine spread in Jatipuro, Jenawi, Jumantono, Karanganyar, Kerjo, Mojogedang and Tawangmangu sub district. Instant herbal medicine al agroindustry is ranked second seed. Instant herbal medicine development strategy include: Increasing the ability of producers in diversifying the instant herbal products at affordable prices the market, increase market access for instant herbal product diversification, increase access to capital through access to financing institutions, development of product diversification while maintaining product quality, increase the ability of producers in access to quality raw materials at affordable prices, increase product quality with local raw materials, especially in terms of capital Strengthening of procurement of raw materials, and development of business partnerships in terms of procurement of raw materials. Business actors in the agroindustry are instant herbal-medicinal and medicinal farmers market vendors as suppliers of raw materials, manufacturers and marketers are as pengolahnya herbal merchants.